Humiliation and liberal democratic politics - Bayefsky, R (2012)
The concept of humiliation has not received much attention from political theorists, despite the fact that themes related to dignity, respect, and honour have become more prominent in recent years. Contributions to the literature in political theory and related disciplines that do focus on humiliation tend to cast humiliation in one particular mould: as a violation of human dignity or equality, or as the emotional response to such a violation. Writers who take this view of humiliation often conclude that liberal democratic states and other actors committed to liberal democratic principles should not engage in humiliation. In this thesis, I provide an in-depth examination of the concept of humiliation, clarifying certain features of humiliation that are presented ambiguously in the current literature. I emphasise the complexity of humiliation and the variety of forms it can take, beyond the violation of human dignity or equality. Humiliation can, for instance, consist of damage to the images of relatively powerful individuals or groups. I then argue that normative conclusions about the responsibilities of actors committed to liberal democratic principles vis-à-vis humiliation ought to be more nuanced than the conclusions found in much of the current literature. In some circumstances, these actors may legitimately engage in action that constitutes and/or leads to humiliation in order to uphold liberal democratic principles. But I also endorse certain concerns regarding this kind of action. Decisions about the proper approach to humiliation on the part of actors committed to liberal democratic principles should be made, I argue, with sensitivity to the particular political context.